ANALISIS KINERJA PENURUNAN DEFORESTASI DI 10 IZIN HUTAN DESA KECAMATAN BATU AMPAR - Denni Nurdwiansyah; Gusti Hardiansyah; Emi Roslinda (Universitas Tanjungpura, 2021)
The effectiveness of devolution policies through social forestry programs in village forest schemes is still being debated at regional, national, and international levels. It departs from the fact that the community has limited resources in managing forests in the long run (35 years). The background of this research is to measure the implementation of devolution policy in 10 granted village forest licenses in the sub-district of Batu Ampar, Kubu Raya District, and its relationship with deforestation rates. The study was conducted by survey method and data collection with literature studies and observations. Observation aims to measure the biophysical condition of the forest as well as the social and economic conditions of the community in the village. The data is processed and analyzed using spatial analysis and performance analysis. The results showed that the devolution policy through the issuance of 10 village forest licenses was proven to be able to improve performance in reducing deforestation, especially after one year of the village forest permits were granted. Keywords: devolution, social forestry, village forest, deforestation, performance AbstrakEfektifitas kebijakan devolusi melalui program perhutanan sosial skema hutan desa masih menjadi perdebatan di level regional, nasional, dan internasional. Hal ini berangkat dari fakta keterbatasan sumber daya yang dimiliki masyarakat dalam mengelola hutan dalam jangka waktu panjang (35 tahun). Penelitian bertujuan untuk mengurai implementasi kebijakan devolusi di 10 izin hutan desa Kecamatan Batu Ampar, Kabupaten Kubu Raya, dan pengaruhnya terhadap laju deforestasi. Penelitian dilakukan dengan metode survei. Pengumpulan data dengan studi literatur dan observasi. Observasi bertujuan untuk mengetahui kondisi biofisik hutan serta kondisi sosial dan ekonomi masyarakat di desa. Data-data diolah dan dianalisis menggunakan analisis spasial dan analisis kinerja. Hasil penelitian menunjukan kebijakan devolusi melalui pemberian 10 izin hutan desa telah terbukti secara kumulatif mampu meningkatkan kinerja positif dalam penurunan deforestasi, terutama setelah satu tahun izin hutan desa diberikan.Kata kunci: devolusi, perhutanan sosial, hutan desa, deforestasi, kinerja